Germline Mutations in BRCA1 and BRCA2 in Breast Cancer Patients with High Genetic Risk in Turkish Population. (1st January 2019) - Geredeli, Caglayan; Yasar, Nurgul; Sakin, Abdullah
Abstract : Background . The guidelines recommend considering the BRCA1 and BRCA2 germline mutations in female patients with breast carcinomas. In this retrospective study, the BRCA1/2 mutation prevalence in high-risk breast carcinoma patients in a Turkish population was investigated. Materials and Methods . In high genetic risk breast carcinoma patients, the BRCA1 and BRCA2 germline mutations were identified by applying next-generation sequencing. Results . The results showed BRCA1/2 mutations in 19% of the total patients. In those with first-degree relatives with breast carcinoma histories, the BRCA1/2 mutation prevalence was also 19%. In the patients younger than 40 years old, the BRCA1/2 mutation prevalence was 19.5%. In the triple-negative breast carcinoma patients younger than 60 years old, the BRCA1/2 mutation prevalence was 24.2%. In the patients younger than 40 years old with triple-negative breast carcinomas, BRCA1/2 mutation positivity was found in 37.5% of the patients. Overall, in the Turkish population, the BRCA1/2 mutation prevalence ranges from 19% to 37% in patients with high-risk breast carcinomas. Conclusion . It is recommended to check for BRCA1/2 mutations in all high-risk breast carcinoma patients in the Turkish population.